Nuclear envelope of the seminal-vesicle epithelium. - Veneziale, C M (1981)
The nuclear envelope of seminal-vesicle epithelium was isolated by a procedure involving enzymic digestion with deoxyribonuclease I, sonication in the presence of 0.34 M-sodium citrate, and centrifugation through sucrose density gradients. The mass of envelope DNA was only 0.8% of that of envelope protein, and by transmission electron microscopy the envelope was 98-99% pure. We showed that the envelope possess a protein kinase activity which is uninfluenced by cyclic nucleotides. Both lysine-rich histone and dephosphophosvitin as substrates gave a greater specific activity than did envelope protein itself. Optimum requirements with respect to Na+, Mg2+, pH and ATP were established for each substrate, and the influence of other factors on enzyme activity was investigated. Data, obtained mainly with the use of lysine-rich histone, are presented which indicate that nuclear envelope from intact and 96 h-castrated guinea pigs may have equal protein kinase activities and, in separate experiments, equal phosphoprotein phosphatase activities. Clarification of these initial observations must await identification of the natural substrates or the envelope's phosphorylation-dephosphorylation reactions.